A Randomized, Placebo Controlled Study of Peri-Operative Pregabalin for Early and Late Post-Operative Pain in Patients Undergoing Open Urological Surgery - Pratik B Tantia; Malik, Sunny; Patel, Bhupesh; Tantia, Ruchi (Asian Journal of Medical Research, 2021)
Introduction: Pregabalin has been used in the peri-operative period for a variety of surgeries and in variable doses. Some studies favor while others refute its role as a pre-emptive and protective analgesic. We hypothesized that Pregabalin would reduce the severity of acute post-operative pain as well as chronic post-surgical pain. Subjects and Methods: A randomized double-blind placebo-controlled study including a total of 120 patients was designed to find the efficacy and safety of Pregabalin in reducing acute as well as chronic post-surgical pain after open urological surgery. Results: The time to rescue analgesic (NRS > 4) was 356.2+101.3 minutes in study group and 267.2+67.79 minutes in control group (p< 0.01). The total dose of rescue analgesic required (mg of Tramadol) in study group (320 + 50.5 mg) was less than the control group (462 + 35.4 mg). Conclusion: Oral Pregabalin was effective in reducing the severity of acute post-operative and chronic post-surgical pain and reducing the dose of rescue analgesic required. However, the incidence of side effects, though minor, was higher in the study group.